Sec8 specifically interacts with the PDZ2 domain of synapse associated protein 102 (SAP102) - Korbula, Katharina; Hammerschmid, Iana; Lesigang, Johannes; Dong, Gang (Frontiers in Cell and Developmental Biology, 2023)
The exocyst is an evolutionarily conserved protein complex tethering secretory vesicles before their docking and fusion with the plasma membrane. The complex also plays important roles in cell migration, synaptogenesis, and neurite outgrowth. One of its subunits, Sec8, was reported to interact with two major synaptic scaffolding proteins SAP102 and PSD-95 that share high sequence homology and contain three PDZ domains at their N-terminal region. The interaction is via the binding of the C-terminal ITTV motif in Sec8 to the PDZ domains of the two synaptic proteins. However, it remains elusive to which PDZ domain(s) Sec8 binds and how their interaction occurs. Here we reported a 2.5 Å resolution crystal structure of the C-terminal half of rat Sec8 containing the ITTV motif. The structure shows that Sec8 contains an enormously long helix at its C-terminus, which bears a unique long “spacer” of 14 residues to bridge the ITTV motif to the compact core of Sec8. We found that Sec8 preferentially binds PDZ2 over PDZ1 and PDZ3 of SAP102. Deletion of the spacer completely abolished the binding of Sec8 to SAP102. Overall, our structural studies, biochemical data and modeling analyses altogether provide an explanation for how Sec8 interacts with SAP102.